2006
DOI: 10.1103/physrevd.73.034020
|View full text |Cite
|
Sign up to set email alerts
|

Light cone sum rules forγ*NΔtransition form factors

Abstract: A theoretical framework is suggested for the calculation of N ! transition form factors using the light-cone sum rule approach. Leading-order sum rules are derived and compared with the existing experimental data. We find that the transition form factors in a several GeV region are dominated by the soft contributions that can be thought of as overlap integrals of the valence components of the hadron wave functions. The minus components of the quark fields contribute significantly to the result, which can be re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
92
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 111 publications
5
92
1
Order By: Relevance
“…[34,35] it has been shown that it is possible to disentangle the contribution to Π µν due to Eq. (44) and Eq.…”
Section: Contribution Of Pγ → ∆ + To the Correlation Functionmentioning
confidence: 99%
See 4 more Smart Citations
“…[34,35] it has been shown that it is possible to disentangle the contribution to Π µν due to Eq. (44) and Eq.…”
Section: Contribution Of Pγ → ∆ + To the Correlation Functionmentioning
confidence: 99%
“…However, it is known that the correlation function is plagued by transitions pγ → N * [34,35], where |N * is a isospin-3 2 spin-1 2 state with negative parity. It is advantageous to use the Lorentz structures that do not receive contributions due to transitions to spin-1 2 − states.…”
Section: Contribution Of Pγ → ∆ + To the Correlation Functionmentioning
confidence: 99%
See 3 more Smart Citations